Preconception folic acid supplementation for the prevention of birth defects: a prospective, population-based cohort study in mainland China - Qiongjie Zhou; Guiying Dong; Qiaomei Wang; Haiping Shen; Yiping Zhang; Shikun Zhang; Jingqi Chen; Xiaotian Li (BMC Pregnancy and Childbirth, 2024)
Abstract Background Folic acid supplementation is recommended for reducing the risk of birth defects. We aimed to assess the protective association of periconception folic acid supplements with birth defects in real-world setting. Methods This prospective, population-based cohort study utilized national preconception registered data of married Chinese couples planning a pregnancy within 6 months between 2010 and 2012 in Mainland China. Participated women are freely provided folic acid starting 3 months before conception till 3 months after conception. Birth defects were self-reported at 42 days postpartumn followup. R software (v4.0.2) was applied for statistical analyses. Results Complete data of 567,547 couples with pregnancy outcomes and folic acid supplementation were extracted for final analysis. A total of 74.7% women were with folic acid supplementation, and 599 birth defects were self-reported. The odd of birth defects was lower among women taking folic acid compared to their counterparts not taking (0.102% vs 0.116%, P < 0.001). In the multiple logistic regression analyses, the odd of birth defects was lower among couples with maternal folic acid supplementation (OR = 0.78, 95%CI: 0.66–0.95, P = 0.011), especially decreased odd of neural tube defects (NTDs) (OR = 0.56, 95%CI: 0.39–0.82, P = 0.003). This association was confirmed by 1:4 and 1:10 case control analysis. Odds of birth defects were significantly lower among women with folic acid supplementation more than 3 months before pregnancy (P < 0.001), and moreover, the odds of cleft (P = 0.007) and NTDs (P = 0.007) were of notable decrease. Conclusion This retrospective case cohort study provides programmatic evidence for public health strategy-making to for reducing the risk of NTDs and clefts.